Design of Chronomodulated Drug Delivery System of Valsartan: In Vitro Characterization - Sokar, M. (Indian J Pharm Sci, 2015)
The aim of the present study was to design and evaluate a chronomodulated time-clock pulsatile tablets of valsartan to release it after a certain lag time, independent of the gastrointestinal pH, in its absorption window to cope with the circadian rhythm of human body for blood pressure elevation. Core tablets were prepared by direct compression of a homogenous mixture of valsartan, Avicel PH101, croscarmellose sodium, magnesium stearate and Aerosil. The core tablets were then sprayed coated with a sealing layer formed of ethyl cellulose that was subsequently coated with a release-controlling layer. Three different aqueous dispersions namely; carnauba wax or beeswax or a mixture in a ratio of 2.5:1, respectively, were used to form five time-clock tablet formulations having the release controlling layer with different thickness {B5, B10, B20, BW5 and CW5}. Quality control testing were carried out to the core tablets. Differential scanning calorimetry was also performed to detect the possible drug excipient interaction in the core tablet formulation. The release was carried out, for the prepared time-clock tablet formulations, in 0.1 N hydrochloric acid for the first 2 h, followed by phosphate buffer (pH 6.8) for 4.5 h. The effect of pH on valsartan release was studied through a release study in 0.1 N hydrochloric acid for 6.5 h. Two phase dissolution study was performed to the selected time-clock tablet formulation to predict the drug permeation through the gastrointestinal tract. Stability study of the selected formula was performed at 25°/60% RH and at 40°/75% RH for 3 months. Results showed that a release-controlling layer composed of a mixture of carnauba wax and beeswax in a ratio of 2.5:1 showed a reasonable release lag time. The release lag time of the tablets increased with the increase of the coat thickness, thus B20>B10>B5 with corresponding lag time values of 4.5, 3 and 2.5 h, respectively. Selected B5 tablet formula exhibited a reasonable lag time after which the highest, complete % drug release at pH 6.8 was obtained. In addition, a good partitioning of valsartan, between the aqueous and organic phases in a ratio of 1:7, was observed. The selected formula was stable for at least 3 months under standard long-term and accelerated storage conditions. In conclusion, in vitro studies revealed that the novel time-clock system could be used successfully to deliver valsartan in a pulsatile pH-independent manner. It provided a desirable lag time followed by a rapid and complete drug release accompanied by an expected effective permeation through the biological membranes upon release in the duodenum; the window of absorption, as indicated by the two phase release study.